Development Of Physics Props For Arduino Uno-Based Light Wavelength Gauges With Diffraction Lattice Method (Case Study of Visible Light Wavelengths) - Rena Herdiana; Aripin Aripin; Ifa Rifatul Mahmudah (Jurnal Pembelajaran Fisika, 2022)
Research has been carried out on the development of physics props for measuring light wavelengths based on Arduino Uno with the diffraction lattice method (case study of visible light wavelengths), with the aim of determining the level of validity and practicality of arduino uno-based light wavelength measuring physics props with the diffraction lattice method. This research includes development research, with reference to the ADDIE development model with stages, namely analysis, design, development, implementation, and evaluation. The testing of props is carried out with validity tests by media experts and material experts to determine the level of validity of the props that have been developed. In addition, product trials were also carried out to determine the level of practicality of teaching aids, through student response tests and assessments from physics teachers. Product trials were carried out at sma class XI MIPA with a total sample of 163 people. Based on the results of the validity test of media experts and material experts, it can be known that the level of validity of props is on very valid criteria with a percentage of 85.71% from media experts and 95.69% from material experts. Then, based on the results of practicality tests carried out through student response tests, it can be known that the level of practicality of teaching aids is on practical criteria, with a percentage of 78.74%. Meanwhile, based on the results of practicality tests conducted through physics teacher assessments, it can be known that the level of practicality of teaching aids is on very practical criteria with a percentage gain of 84.28%. Based on the results of this study, it can be concluded that the physics props of arduino uno-based light wavelength measuring with the diffraction lattice method meet the criteria very valid and practical for use in the physics learning process.Keywords: Physics Props, Arduino Uno, Light Wave, Diffraction grid.DOI: http://dx.doi.org/10.23960/jpf.v10.n2.202207